Wetland evolution in the Qinghai Lake area, China, in response to hydrodynamic and eolian processes during the past 1100 years. (15th April 2017) - Yan, Dada; Wünnemann, Bernd; Hu, Yanbo; Frenzel, Peter; Zhang, Yongzhan; Chen, Kelong
Abstract: The Daotanghe riverine wetland in close proximity to the Qinghai Lake was investigated to demonstrate the interrelationships between Qinghai Lake hydrodynamic processes, eolian mobility and ecological conditions during the past 1100 years in response to climate change. We used ostracod assemblages from various sites east of Qinghai Lake and from the sediment core QW15 of Daotanghe Pond and combined them with grain size and geochemical data from the same core. The statistical extraction of grain size endmembers (EM) revealed three different transportation processes responsible for pond-related fluvio-lacustrine, pure fluvial and eolian deposits. Identified seasonal effects (eolian mobility phase) and timing of ice cover are possible tracers for the competing influence between the Asian summer monsoon and the Westerlies in the Daotanghe Wetland and surrounding area. Our results show that ostracod associations and sediment properties are evidence of a fluvio-lacustrine fresh water environment without ingression of Qinghai Lake into the wetland. Hydrodynamic variations coupled with phases of eolian input indicate highly variable water budgets in response to climate-induced effective moisture supply. The Medieval Warm Period (MWP) until about 1270 CE displays generally moist and warm climate conditions with minor fluctuations, likely in response to variations in summer monsoon intensity. The three-partite period of the Little Ice Age (LIA), shows hydrologically unstable conditions between 1350 and 1530 CE with remarkably colder periods, assigned to a prolonged seasonal ice cover. Pond desiccation and replacement by fluvial deposits occurred between 1530 and 1750 CE, superimposed by eolian deposits. The phase 1730–1900 CE is recorded by the re-occurrence of a pond environment with reduced eolian input. Principal Component Analysis (PCA) on ostracod abundances shows similar trends. All three phases of the LIA developed during a weak summer monsoon influence, favoring westerly-derived climate conditions until ca. 1850 CE, in accordance with records from the adjacent regions. Seasonal freezing periods in excess of the average time of frozen water bodies also occurred in periods of the well-known grand solar minima and indicate stronger seasonality, possibly independent from variations in summer monsoon strength but with links to global northern hemispheric climate. Highlights: Depositional processes in the wetlands are strongly linked with seasonal effects during the last 1100 years. Two seasonal effects are direct responses to the interplay between the Asian summer monsoon and Westerlies. The MWP experienced warm-wet conditions under summer monsoon control, the LIA was influenced by westerly-derived climate. Morpho- and hydrodynamic variations seem to coincide with northern hemispheric solar forcing.